Risk Factors of Postoperative Wound Infection at Mitra Pedan Public Hospital, Klaten, Central Java Province - Mujiyono, Mujiyono; Sukesi, Tri Wahyuni; Ruliyandari, Rochana (PROMOTOR, 2024)
Hospitals are very complex health service units with various elements. This will make it easier for cross-infections to occur in patients due to germs, and viruses. These infections are known as nosocomial infections and one of them occurs as a result of surgery which is often known as postoperative wound infection. Many risk factors cause infection such as patient factors, procedure-related factors, facilities, patient preparation, intra-operative factors, and other factors (waiting time for surgery). The incidence of postoperative wound infection in the last 2 years at Mitra Pedan Public Hospital was 2.28% in 2022 and 2% in 2023 which exceeded the standard from the Ministry of Health, namely ≤ 1.5%. This study aimed to analyze the risk factors of postoperative wound infection. This research uses quantitative research with an analytical observational research design and a cross-sectional approach. The test analysis used is the chi-square test and logistic regression. The research was conducted from January to February 2024. The results from the multivariate analysis on the variable duration of hospitalization obtained a p.value of 0.045 (AOR: 4.299, 95%CI: 1.049-17.618) and the variable duration of surgery obtained a p.value of 0.001 (AOR: 8.623, 95%CI: 2.373-31.326). Conclusion: there is no relationship between sterilization of the operating room, BMI, and time of antibiotic administration with postoperative wound infections. Meanwhile, the risk factors found are the duration of the operation and the duration of hospitalization. Hospital management must pay more attention to the duration of operation and length of hospitalization to minimize the incidence of postoperative wound infections.